Involvement of steroids in anti-inflammatory effects of PK11195 in a murine model of pleurisy - Marcelo Barreto Spillere da Silva; Roseli Coimbra Farges; Tânia Silvia Fröde (Mediators of Inflammation)
BACKGROUND: Studies on peripheral benzodiazepine receptor function have yielded a diverse list of activities of which the anti-inflammatory effects need to be further examined.